Zone of Technogenic Pollution of the Pervouralsk-Revda Industrial Hub: Soil Assessment and Land Use Issues - GUSEV, Alexey S.; BAYKIN, Yuri L.; VASHUKEVICH, Nadezhda V.; BELICHEV, Alexey A. (Journal of Environmental Management and Tourism; Vol 11 No 5 (2020): JEMT Volume XI Issue 5(45) Fall 2020DO - 10.14505//jemt.v11.5(45).03, 2020)
The influence of heavy metals pollution of soils and lands in the zone of metallurgical plants influence in the Sverdlovsk region (Russia) was analyzed. Sredneuralsk Copper Smelting Plant (SUMZ) is an environmental polluter with copper, lead, zinc, cadmium and sulfur oxides, nitrogen and hydrogen fluoride. Pervouralsk plant for production of chromium-containing materials ("Crompick") generates emissions of chromium compounds and other heavy metals. Environmental risk was assessed using the Zc pollution index adopted by the Russian regulations and the soil buffering index to heavy metals. The data on the reaction of different organization-levelled bioindicators in the system “polluted soil-biota” is given. The materials obtained during assessment of the arable soils contamination in the zone of Pervouralsk-Revda industrial hub showed that the levels of concentration of heavy metals in soils to a large extent correlated with both the composition of industrial emissions and the range of sampling from pollution sources. The maximum level of contamination (Zc index 263-546) was detected in arable soils at a distance of 1.5 km from the SUMZ. The "Crompick" enterprise has a less significant identified impact on the contamination of arable soils. “Extremely dangerous” soil contaminations (index Zc 134) were detected only at a distance of 0.5 km from it. The results of our model experiments allowed us to conclude that the safest level of pollution, when the critical concentration of heavy metals does not accumulate in plants, is the Zc index value below 12. In accordance with the current level of pollution in the survey area, restrictions on the main land use categories were proposed.